2017
DOI: 10.3390/ijms18061297
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Mechanism in Anti-Cancer Immunity: Its Pros and Cons for Cancer Therapy

Abstract: Autophagy, a self-eating machinery, has been reported as an adaptive response to maintain metabolic homeostasis when cancer cells encounter stress. It has been appreciated that autophagy acts as a double-edge sword to decide the fate of cancer cells upon stress factors, molecular subtypes, and microenvironmental conditions. Currently, the majority of evidence support that autophagy in cancer cells is a vital mechanism bringing on resistance to current and prospective treatments, yet whether autophagy affects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 162 publications
0
30
0
Order By: Relevance
“…Accumulating convincing evidence over several decades has shown that the effectiveness of anti-cancer therapies is not only caused by apoptosis, but also involves autophagy [37,38]. Therefore, detecting autophagy-associated regulators may be a potential strategy for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating convincing evidence over several decades has shown that the effectiveness of anti-cancer therapies is not only caused by apoptosis, but also involves autophagy [37,38]. Therefore, detecting autophagy-associated regulators may be a potential strategy for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the roles of autophagy in cancer and cancer treatment remain poorly defined 28 , 37 , 38 . What is increasingly clear is that the mechanisms are likely complex, dynamic, and context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…What is increasingly clear is that the mechanisms are likely complex, dynamic, and context-dependent. Diverse pathways and processes can come into play including autophagy-mediated effects on cell death, cell cycle arrest, tumor promoting inflammation, tumor microenvironments, immunogenicity, immune cell cytotoxicity, and checkpoints 28 , 37 , 38 . In the present study, we hoped to utilize in vitro modeling systems to elucidate the cell autonomous mechanisms in an unbiased manner through combining RNA-seq analysis with TCGA data mining.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, autophagy itself is regulated and influenced by a large number of different proteins and embedded in a variety of molecular networks, pathways, and biological processes [ 7 , 10 ]. The immunology of the tumor-host interaction, for example, has been shown to interact with autophagy [ 46 ] as seen in tumors such as breast cancer [ 47 ] or melanoma [ 48 , 49 ]. Interestingly, none of the autophagy related proteins included in the present study showed an association with the density of intratumoral T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%